The Swedish medical birth register during five decades: documentation of the content and quality of the register - Cnattingius, Sven; Källén, Karin; Sandström, Anna; Rydberg, Henny; Månsson, Helena; Stephansson, Olof; Frisell, Thomas; Ludvigsson, Jonas F. (European journal of epidemiology, 2023)
Pregnancy-related factors are important for short- and long-term health in mothers and offspring. The nationwide population-based Swedish Medical Birth Register (MBR) was established in 1973. The present study describes the content and quality of the MBR, using original MBR data, Swedish-language and international publications based on the MBR. The MBR includes around 98% of all births in Sweden. From 1982 onwards, the MBR is based on prospectively recorded information in standardized antenatal, obstetric, and neonatal records. When the mother and infant are discharged from hospital, this information is forwarded to the MBR, which is updated annually. Maternal data include information from first antenatal visit on self-reported obstetric history, infertility, diseases, medication use, cohabitation status, smoking and snuff use, self-reported height and measured weight, allowing calculation of body mass index. Birth and neonatal data include date and time of birth, mode of delivery, singleton or multiple birth, gestational age, stillbirth, birth weight, birth length, head circumference, infant sex, Apgar scores, and maternal and infant diagnoses/procedures, including neonatal care. The overall quality of the MBR is very high, owing to the semi-automated data extraction from the standardized regional electronic health records, Sweden’s universal access to antenatal care, and the possibility to compare mothers and offspring to the Total Population Register in order to identify missing records. Through the unique personal identity numbers of mothers and live-born offspring, the MBR can be linked to other health registers. The Swedish MBR contains high-quality pregnancy-related information on more than 5 million births during five decades.